Analisis Terhadap Tindak Pidana Penipuan Pada Transaksi Jual Beli Online di Kota Batam - Elza Syarief; Yudhi Priyo Amboro; Uji Febianika (Journal of Judicial Review, 2015)
The technology development in every aspects, in fact the crime was also developing itself, known as cyber crime or the crime by using internet networking. On sell and buy transaction via Online actually it was not missed from the cyber crime.The research problem that would be discuss was (1) how was the implementation of ITE Law against sell-buy transaction fraud by internet in Batam, (2) the problem on implementation of ITE Law against sell-buy transaction fraud by internet in Batam, and (3) what was the best solution to handle sell-buy transaction fraud by internet problem in Batam.This research was using descriptive methode by using normative approach (legal research) to got secondary data and juridic approach (sociologic juridic), to got primary data by field research.According to the research result, ITE Law had been implemented against sell-buy transaction fraud by internet in Batam. The problem that faced by Batam Police Investigator on implementing ITE Law against sell-buy transaction fraud by internet, such ITE Laws was not too clear regulate criminal provisions for the person that had done fraud via internet.The best solution on handling the obstacle to implement ITE Law in Batam was there were need some socialization to all citizens componens to report case against sell-buy transaction fraud by internet in Batam to police. Also needed equipments that useful and a competent human resources to searched the people that done sell-buy transaction fraud by internet in Batam.